Bromine-Chlorine Coupling in the Antarctic Ozone Hole - Sze, Nien-Dak; Rodriquez, Jose M.; Danilin, Michael Y.; Ko, Malcolm K. W.; Prather, Michael J. (1996)
The contribution from the chlorine and bromine species in the formation of the Antarctic ozone hole is evaluated. Since chlorine and bromine compounds are of different industrial origin, it is desirable, from a policy point of view, to be able to attribute chlorine-catalyzed loss of ozone with those reactions directly involving chlorine species, and likewise for bromine-catalyzed loss. In the stratosphere, however, most of the chemical families are highly coupled, and, for example, changes in the chlorine abundance will alter the partitioninig in other families and thus the rate of ozone loss. This modeling study examines formation of the Antarctic ozone hole for a wide range of bromine concentrations (5 - 25 pptv) and for chlorine concentrations typical of the last two decades (1.5, 2.5 and 3.5 ppbv). We follow the photochemical evolution of a single parcel of air, typical of the inner Antarctic vortex (50 mbar, 70 deg. S, NO(sub y) = 2 ppbv, with Polar Stratospheric Clouds(PSC)) from August 1 to November 1. For all of these ranges of chlorine and bromine loading, we would predict a substantial ozone hole (local depletion greater than 90%) within the de-nitrified, PSC- perturbed vortex. The contributions of the different catalytic cycles responsible for ozone loss are tabulated. The deep minimum in ozone is driven primarily by the chlorine abundance. As bromine levels decrease, the magnitude of the chlorine-catalyzed ozone loss increases to take up the slack. This is because bromine suppresses ClO by accelerating the conversion of ClO an Cl2O2 back to HCI. For this range of conditions, the local relative efficiency of ozone destruction per bromine atom to that per chlorine atom (alpha-factor) ranges from 33 to 55, decreasing with increase of bromine.